Ultrasound Applied in the Reduction of Viscosity of Heavy Crude Oil - Olaya-Escobar, David Roberto; Quintana-Jiménez, Leonardo Augusto; González-Jiménez, Edgar Emir; Olaya-Escobar, Erika Sofia (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Reducing the viscosity of heavy oil through upgrading techniques is crucial to maintaining the demand for oil, which is growing at an annual rate of 1.8%. The phenomenon of acoustic cavitation occurs when ultrasound is applied in the treatment of heavy crudes. This is an emerging technology that is being developed to improve the physical and chemical properties of highly viscous crudes, which facilitates handling, increases the proportion of light factions, and improves their price in the market. Taking into account that it does not yet operate on an industrial scale, a bibliographic review of the advances in acoustic cavitation technology with ultrasound for the improvement of heavy crude is justified, to contribute to the development of its industrial application by identifying new approaches and research guidelines in engineering and science. The objective of this article is to show the advance of said technology and describe the experiments carried out by various authors. For this purpose, a literature review was conducted with documents published from 1970 to 2020, which were compiled through a systematic search in academic databases. As a result of this review, some conceptual gaps and deficiencies in the phenomenological foundation were found, which explain the current difficulties to implement experimental tests and design the process at larger scales. These deficiencies limit the quality and repeatability of the results. A need was also identified to focus the efforts on a systematic experimentation that fulfills the laboratory and pilot plant phases, which are essential to take these technologies to an industrial scale.